Corn Cost-Return Budget in Southeast Kansas - O'Brien, Daniel M.; Shoup, Douglas; Dhuyvetter, Kevin C. (My University, 2014)
This publication outlines the expected costs and returns for corn in southeast Kansas.
MF993_2014_02
Keywords: MF993; Economics; Crops; MF